Timing, fragmentation of work and income inequality: An earnings treatment effects approach - Joachim Merz; Paul Böhm; Derik Burgert (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2005)
Traditional welfare analyses based on money income needs to be broadened by its time dimension. In the course of time the traditional full-time work is diminishing and new labour arrangements are discussed (keyword: flexible labour markets). Our study is contributing to economic well-being by adding insights into particular work effort characteristics - the daily timing of work and its fragmentation - and its resulting income distribution. With our focus on - who is working when within a day with which earnings consequences - we go beyond traditional labour market analyses with its working time division into aggregated full and part time work, working hours spread across a week and weekend, life time working etc. Whereas the first part of our study is describing the distribution of timing and fragmentation of daily work time and its resulting income based on more than 35.000 diaries of the recent German Time Budget Survey 2001/2002, the second part of our study quantifies determinants of arrangement specific earnings functions detecting significant explanatory pattern of what is behind. The economic theory behind is a human capital approach in a market and non-market context, extended by non-market time use, the partner's working condition, social networking as well as household and regional characteristics. The econometrics use a treatment effects type interdependent estimation of endogenous participation (selection) in a daily working hour pattern (self-selection)and pattern specific earnings function explanation. The overall result: Individual earnings in Germany are dependent on and significant different with regard to the daily working hour arrangement capturing timing and fragmentation of work time. Market and non-market factors are important and significant in explaining earnings. – – Traditionelle Wohlfahrtsanalysen auf der Basis monetärer Größen erfordern eine Erweiterung um ihre Zeitdimension. Im Laufe der Zeit verringerte sich die Bedeutung von Vollzeitarbeit zugunsten neuer Arbeitsarrangements (Schlagwort: flexible Arbeitsmärkte). Unsere Studie trägt zur ökonomischen Wohlfahrt bei durch die Analyse des spezifischen Arbeitsaufwandes - die tägliche Lage der Arbeitszeit und ihrer Fragmentierung - und seiner resultierenden Einkommensverteilung. Mit unserem Fokus auf Wer arbeitet wann am Tag und mit welchen Einkommenskonsequenzen gehen wir über traditionelle Arbeitsmarktanalysen hinaus, die sich auf aggregierte Voll-und Teilzeitarbeit, wöchentliche Arbeitszeit, Arbeit am Wochenende, Lebensarbeitszeit etc. beschränkt.Während der erste Teil unserer Studie die Verteilung der zeitlichen Lage und Fragmentierung der täglichen Arbeitszeit und der resultierenden Einkommen auf der Basis von mehr als 35.000 Zeittagebüchern der aktuellen deutschen Zeitbudgeterhebung 2001/02 beschreibt, quantifiziert der zweite Teil Determinanten arrangementspezifischer Einkommensfunktionen, um signifikante Erklärungsmuster zu finden. Die zugrunde liegende Theorie ist der Humankapitalansatz in einem markt- und nichtmarktmäßigen Kontext, erweitert um nichtmarktmäßige Zeitallokation, die Arbeitsbedingungen des Partners, soziale Netzwerke als auch Haushalts- und regionale Charakteristika. Der ökonometrische Ansatz ist ein treatment effects-Ansatz mit interdependenter Schätzung der endogenen Partizipation (Selektion) hinsichtlich des täglichen Arbeitszeitmusters (self-selection) und musterspezifischer Erklärung der Einkommen.Herausragendes Ergebnis: Die individuellen Einkommen in Deutschland sind abhängig und signifikant unterschiedlich hinsichtlich der täglichen Arbeitszeitarrangements mit der zeitlichen Lage und Fragmentierung der Arbeitszeit. Markt und nichtmarktmäßige Faktoren sind dabei wichtig und signifikant in der Erklärung der Einkommen.
Keywords: J22; J23; J24; J30; 330; time use and inequality; timing and fragmentation of work time; working hour arrangements; labour supply; earnings explanation; human capital; market and non-market time use; time use diary data; treatment effects modelling; endogenous self-selection; German time budget survey 2001/2002; Zeitverwendung und Ungleichheit; Lage und Fragmentierung der täglichen Arbeitszeit; Arbeitszeitarrangements; Arbeitsangebot; Einkommenserklärung; Humankapital; Markt- und nichtmarktmäßige Zeitverwendung; Zeittagebücher; Treatment effects-Ansatz; endogene Selbst-Selektion; Zeitbudgeterhebung 2001/02; Arbeitszeit; Freizeit; Zeitverwendung; Einkommensverteilung; Arbeitsbedingungen; Arbeitsorganisation; Zeitverwendung; Schätzung; Deutschland